Breakthrough renewables and the green paradox - Van der Ploeg, R (University of Oxford, 2012)
We show how a monopolistic owner of oil reserves responds to a carbon-free substitute becoming available at some uncertain point in the future if demand is isoelastic and variable extraction costs are zero but upfront exploration investment costs have to be made. Not the arrival of this substitute matters for efficiency, but the uncertainty about the timing of this substitute coming on stream. Before the carbon-free substitute comes on stream, oil reserves are depleted too rapidly; as soon as the substitute has arrived, the oil depletion rate drops and the oil price jumps up by a discrete amount. Subsidizing green R&D to speed up the introduction of breakthrough renewables leads to more rapid oil extraction before the breakthrough, but more oil is left in situ as exploration investment will be lower. The latter offsets the Green Paradox.